(untitled) - Lougheed, Lin (Thành phố Hồ Chí Minh, 2016)
The TOEIC Bridge test is an English proficiency exam designed for programs set up to train beginning and intermediate students of the English language. This brand-new man-ual has been designed specifically for those language learners. It is suitable for use by high-school and college-level students, for immigrant language-training programs, and for learners in the workplace.
Keywords: Tiếng Anh,English language; Kỳ thi,Hướng dẫn học,Examinations,Study guides